PCAOB Inspection Reports and Audit Quality - GUNNY, Katherine A. (Institutional Knowledge at Singapore Management University, 2013)
With the creation of the Public Company Accounting Oversight Board (PCAOB), audit firm oversight shifted away from self-regulation to independent regulation. The inspections program is the central feature of the PCAOB. We examine whether PCAOB inspections are able to distinguish actual audit quality (as opposed to perceived) during the period inspected to better understand this important regulatory tool. We use three measures that proxy for actual audit quality: abnormal accruals, restatements, and the propensity to issue a going concern opinion. For triennially inspected auditors, we find that PCAOB inspections are associated with lower audit quality when the reports are seriously deficient (weaker results for deficient reports). More specifically, we find clients of triennially inspected auditors that receive a deficient or seriously deficient report are associated with significantly higher abnormal current accruals and clients of auditors that receive a seriously deficient report are associated with a greater propensity to restate. Our evidence is subject to the caveat that PCAOB reports for triennially inspected auditors do not capture the going concern aspect of audit quality. For annually inspected auditors, the results are conflicting and suggest PCAOB inspection reports do not distinguish audit quality during the period inspected for annually inspected auditors.